7-Bromo-4b-methyl-7,8-dihydro-4bH-9-thia-8a-azafluorene 9,9-dioxide - Gallucci, Judith C. (International Union of Crystallography, 2008)
The title compound, C(12)H(12)BrNO(2)S, was isolated after direct irradiation (hν 350 nm, hexane) of a mixture of stereoisomeric sulfonamides containing a vicinal dibromide and a conjugated diene. This product is one of a group of substrates that has contributed to our understanding of the photoreactivity patterns of non-bridged sulfonamides. The crystal structure was determined from a non-merohedrally twinned data set, where the twin law corresponded to a 180° rotation about the a* axis. The minor twin component refined to a value of 0.176 (3). The conformation of the molecule is planar at one end, as the benzene ring and the adjacent fused five-membered ring are coplanar, and U-shaped at the other end, where the five-membered ring is fused to the heterocyclic six-membered ring containing an allyl bromide group.